2018
DOI: 10.1007/s00167-018-5251-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies for ischiofemoral impingement: a systematic review

Abstract: Your article is published under the Creative Commons Attribution license which allows users to read, copy, distribute and make derivative works, as long as the author of the original work is cited. You may selfarchive this article on your own website, an institutional repository or funder's repository and make it publicly available immediately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 42 publications
(146 reference statements)
1
31
0
Order By: Relevance
“…Posterior hip pain can be relieved by the resection and remodeling of the lesser trochanter of the femur. Preoperative and postoperative imaging evaluations have revealed an enlarged IFS and QFS, which have become specific indicators for evaluating IFI (1,14). In the present study, it was observed that the IFS and QFS changed dynamically with the change in position.…”
Section: Discussionsupporting
confidence: 54%
“…Posterior hip pain can be relieved by the resection and remodeling of the lesser trochanter of the femur. Preoperative and postoperative imaging evaluations have revealed an enlarged IFS and QFS, which have become specific indicators for evaluating IFI (1,14). In the present study, it was observed that the IFS and QFS changed dynamically with the change in position.…”
Section: Discussionsupporting
confidence: 54%
“…A recent systematic review on the treatment strategies for ischiofemoral impingement revealed that several treatment strategies had been reported for ischiofemoral impingement, and most of them had good short- to medium-term outcomes with a low rate of complications. However, there were no comparative studies to assess the superiority of one technique over another, thus further research was recommended [ 26 , 27 ]. Hence, due to the limited understanding of the condition, preventive action in sports and the mechanism behind success of conservative treatment remains unelicited.…”
Section: Introductionmentioning
confidence: 99%
“…Although these pathologies are all located in the deep gluteal space, 3 SNE, IFI, and proximal hamstring tears are unique entities. [4][5][6][7][8] Kay et al 6 performed a systematic review that assessed complications following SNE surgical management. These authors reported that the endoscopic alternative resulted in an astonishingly low incidence of complications with a rate less than 1%.…”
Section: See Related Article On Page 2152mentioning
confidence: 99%
“…These authors reported that the endoscopic alternative resulted in an astonishingly low incidence of complications with a rate less than 1%. Regarding IFI, Nakano et al 8…”
Section: See Related Article On Page 2152mentioning
confidence: 99%